PTPIP51: A New Interaction Partner of the Insulin Receptor and PKA in Adipose Tissue - M. A. Bobrich; S. A. Schwabe; A. Brobeil; M. Viard; M. Kamm; F. C. Mooren; K. Krüger; C. Tag; M. Wimmer (Journal of Obesity, 2013)
Aims. Our previous experiments revealed an association of PTPIP51 (protein tyrosine phosphatase interacting protein 51) with the insulin signalling pathway through PTP1B and 14-3-3beta. We aimed to clarify the role of PTPIP51 in adipocyte metabolism. Methods. Four groups of ten C57Bl/6 mice each were used. Two groups were fed a standard diet; two groups were fed a high-fat diet. Two groups (one high-fat diet and one standard diet) were submitted to endurance training, while the remaining two groups served as untrained control groups. After ten weeks, we measured glucose tolerance of the mice. Adipose tissue samples were analyzed by immunofluorescence and Duolink proximity ligation assay to quantify interactions of PTPIP51 with either insulin receptor (IR) or PKA. Results. PTPIP51 and the IR and PTPIP51 and PKA, respectively, were colocalized in all groups. Standard diet animals that were submitted to endurance training showed low PTPIP51-IR and PTPIP51-PKA interactions. The interaction levels of both the IR and PKA differed between the feeding and training groups. Conclusion. PTPIP51 might serve as a linking protein in adipocyte metabolism by connecting the IR-triggered lipogenesis with the PKA-dependent lipolysis. PTPIP51 interacts with both proteins, therefore being a potential gateway for the cooperation of both pathways.